The Berenstain Bears, no girls allowed - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1986)
Annoyed that Sister Bear always beats them at baseball and other "boy" type activities, her brother and the other male cubs try to exclude her from their new club.
AD 560
Adult 560
Accelerated Reader AR
Keywords: Sex role -- Fiction; Brothers and sisters -- Fiction; Clubs -- Fiction; Bears -- Fiction